Is “ai” a Unitary or Separate Morpheme? - Fáladé Ọpéyemí Williams (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
Yorubá is one of the major languages spoken in Nigeria alongside Hausa and Igbo. It has enjoyed extensive research works from both native and non-native authors in virtually all the sub-fields of linguistics. However, there are areas of disagreement among scholars, one of which is the status of the negative maker "ai" as a morpheme or two morphemes. This argument, among other reasons, prompted this paper. Albeit, Oye (2007) argues that negative marker /ai/ is a morpheme while Awobuluyi (2005), Adewole (1992) Solomon (1983) and Olumuyiwa (2006) have a contrary opinion, they claim that the negative prefix marker /ai/ is two morphemes. In this paper, we shall examine the arguments of Yoruba scholars on the negative prefix marker /ai/ as to whether it a unitary morpheme or two separate morphemes. We shall argue in this paper, that the morpheme /i/ has two variants; one is a nominal prefix while the other is a negative marker and the variants are in complementary distribution. We shall also show in this paper that /a/ is a nominal prefix while /i/ is the negative marker in support of the earlier scholars that claim that /ai/ is two morphemes.